Biossensores baseados no processo de inibição enzimática - Brasil de Oliveira Marques, Paulo Roberto [UNESP]; Yamanaka, Hideko [UNESP] (Soc Brasileira Quimica, 2008)
Fast, selective, reproducible and reliable detections have been carried out by using enzymatic biosensors in several areas. The enzymatic biosensors based on the inhibition represent an important role in analytical chemistry. Enzymes like cholinesterases, peroxidases, tyrosinases, etc. have been immobilized on electrochemical and optical transducers and the enzymatic activity decreasing in the presence of the inhibitor is related with its concentrations. This article presents a review on the enzymes used on the construction of these sensors, emphasizing the respective applications.
Biosensors based on the enzymatic inhibition process
Keywords: enzymatic biosensor; enzymatic inhibition; bio-electrochemistry